2022
DOI: 10.24191/apmaj.v17i1-02
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Resource Constraint Issues: Unpacking The Strategies for Sustainability of Nonprofit Organisations

Abstract: Nonprofit organisations (NPOs) play a significant role in social service delivery via deliverables of the organisational mission. However, NPOs operate with limited resources, which consequently trigger their unsustainability. The inability of NPOs to address resource constraint issues may adversely impact society because they play an important role in delivering social services and ensuring sustainable development. Hence, through semi-structured interviews, this study addressed how NPOs operating under limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Since 2014, only very few papers have been published which refer explicitly to SMCP and environmental sustainability in NPOs. If one takes a look at the existing literature on SMCP and environmental sustainability in NPOs and NGOs, it becomes apparent that the focus of the papers has been on selective SMCP in NPOs and NGOs [ [27] , [40] , [41] , 42 , 43 , 44 , 45 , 46 , 47 , 15 , 48 ]. The main topics of the research on sustainability management in general are: Partnerships and collaborations [ 27 , 40 , 42 , 43 , 45 , 46 , 48 ]: These articles show, how NPOs and NGOs promote sustainability through strategic partnerships and collaborations.…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014, only very few papers have been published which refer explicitly to SMCP and environmental sustainability in NPOs. If one takes a look at the existing literature on SMCP and environmental sustainability in NPOs and NGOs, it becomes apparent that the focus of the papers has been on selective SMCP in NPOs and NGOs [ [27] , [40] , [41] , 42 , 43 , 44 , 45 , 46 , 47 , 15 , 48 ]. The main topics of the research on sustainability management in general are: Partnerships and collaborations [ 27 , 40 , 42 , 43 , 45 , 46 , 48 ]: These articles show, how NPOs and NGOs promote sustainability through strategic partnerships and collaborations.…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
“…Partnerships and collaborations [ 27 , 40 , 42 , 43 , 45 , 46 , 48 ]: These articles show, how NPOs and NGOs promote sustainability through strategic partnerships and collaborations. By collaborating with different entities, resources are pooled, impact is amplified and innovation is encouraged.…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
“…However, corporations are increasingly getting involved in community assistance through charitable efforts (Cibrario & Ciambra, 2019). Despite the various backgrounds and investments of these organisations engaged in supporting projects, the author contends that their overarching aim, irrespective of their geographical presence, should be to strive for sustainable philanthropic endeavours (Ab Samad & Ahmad, 2022;Hopkins, 2019). The empirical study of Jiang et al (2021) found that combining stringent social distancing measures with comprehensive income support programmes was particularly effective in reducing COVID-19 cases and deaths, especially in countries with limited socioeconomic resources and healthcare infrastructure.…”
Section: Sustainable Social Interventionmentioning
confidence: 99%